Rethinking Husband’s Consent in Abortion Decisions: Legitimacy and Authority in Islamic Legal Perspective - Siti Hamidah; Ali Raza Akbar (Athallah Publishing, 2026)
This study critically examines the role of husband’s consent in abortion decisions from the perspective of Islamic law, with particular emphasis on the concepts of legitimacy and authority. While classical Islamic jurisprudence recognizes the husband’s position within the marital relationship, contemporary debates increasingly question the extent to which such authority should influence women’s reproductive rights. This research seeks to explore whether the requirement of husband’s consent constitutes a legitimate legal norm or reflects socio-cultural interpretations that extend beyond foundational Islamic legal principles. Using a normative and socio-legal approach, this study analyzes classical and contemporary Islamic legal texts, including Qur’anic interpretations, hadith, and scholarly opinions across different schools of thought, alongside contemporary legal practices in Muslim-majority societies. The findings reveal that there is no unanimous consensus among Islamic jurists regarding the necessity of husband’s consent in abortion, particularly in cases involving health risks, early-stage pregnancy, or emergency conditions. Instead, the requirement often emerges from patriarchal interpretations and socio-cultural constructs rather than explicit legal mandates. Furthermore, the study highlights a growing tension between traditional notions of male authority and evolving understandings of women’s autonomy and bodily integrity. It argues that the legitimacy of husband’s consent must be re-evaluated within a broader framework of justice (maqāṣid al-sharīʿah), which prioritizes the protection of life, dignity, and well-being.